2023
DOI: 10.1021/acs.orglett.3c02583
|View full text |Cite
|
Sign up to set email alerts
|

Daldipyrenones A–C: Caged [6,6,6,6,6] Polyketides Derived from an Endolichenic Fungus Daldinia pyrenaica 047188

Seungjin Lee,
In Guk Park,
Jin Won Choi
et al.

Abstract: polyketides featuring a spiro-azaphilone unit, were discovered from an endolichenic fungus, Daldinia pyrenaica 047188. The structures of 1−3 were determined by using spectroscopic analysis and chemical derivatization. Daldipyrenones are likely derived by combining a chromane biosynthesis intermediate, 1-(2,6-dihydroxyphenyl)but-2-en-2-one, and a spiro-azaphilone, pestafolide A, via radical coupling or Michael addition to form a bicyclo[2.2.2]octane ring. Genome sequencing of the strain revealed two separate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Among them, ulosporins A-G (17-23b) were reported as new compounds for the first time. The other six benzoquinone compounds, 2-acetonyl-3-methyl-5-hydroxy-7-methoxynaphthazarin (24), 6-deoxy-3,4anhydrofusarubin (25), ascomycone A (26), ascomycone B (27), and 6-deoxybostrycoidin (28) were revealed as known compounds. A bioactivity assay test showed that ulosporin G (23) significantly inhibited the growth of the human cancer cell lines A549, MCF-7, and KB tumor cells, with IC 50 values of 1.3, 1.3, and 3.0 µM, respectively.…”
Section: Simple Aromatic Polyketidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, ulosporins A-G (17-23b) were reported as new compounds for the first time. The other six benzoquinone compounds, 2-acetonyl-3-methyl-5-hydroxy-7-methoxynaphthazarin (24), 6-deoxy-3,4anhydrofusarubin (25), ascomycone A (26), ascomycone B (27), and 6-deoxybostrycoidin (28) were revealed as known compounds. A bioactivity assay test showed that ulosporin G (23) significantly inhibited the growth of the human cancer cell lines A549, MCF-7, and KB tumor cells, with IC 50 values of 1.3, 1.3, and 3.0 µM, respectively.…”
Section: Simple Aromatic Polyketidesmentioning
confidence: 99%
“…8331C [22], and the new compounds biatriosporins G-L (2-7) were reported for the first time in nature. The other anthraquinones were identified as 6-O-demethyl-5-deoxyfusaru- Moreover, thirteen benzoquinone derivatives (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) were isolated from the lichen endophytic fungus Ulospora bilgramii 8344B in 2020 [24]. Among them, ulosporins A-G (17-23b) were reported as new compounds for the first time.…”
Section: Simple Aromatic Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research groups that seek to discover novel bioactive molecules mainly collect samples from undisclosed or unique sources that cannot be easily accessed, such as the Arctic and deep sea. However, in crowded areas, various factors such as physical forces from people walking on soil, changes in pH by pollutants, and the presence of other harmful organisms can act as elicitors on soil microorganisms, leading to the expression of silent genes and the biosynthesis of novel molecules. The Natural Products Drug Discovery research group (NPDD) at Duksung Women’s University has isolated fungal strains from soil samples obtained from not only urban areas but also unusual environments in South Korea. Inspired by the University of Oklahoma Citizen Science Soil Collection Program, we have recruited volunteers (students) to collect soil samples from residential areas and tourist attractions during travel.…”
mentioning
confidence: 99%
“…The fungus Daldinia pyrenaica 047188, obtained from the lichen Myelochroa aurulenta , produces daldipyrenone A 15 that has a novel pentacyclic ring system. 14 The authors propose that daldipyrenone A 15 is formed from two polyketide precursors. Hyperelatolide A 16 , from Hypericum elatoides , has an unusual carbon skeleton that was confirmed by X-ray analysis.…”
mentioning
confidence: 99%